2018
DOI: 10.1080/16000870.2018.1481690
|View full text |Cite
|
Sign up to set email alerts
|

Adding new evidence to the attribution puzzle of the recent water shortage over São Paulo (Brazil)

Abstract: São Paulo, Brazil has experienced severe water shortages and record low levels of its water reservoirs in 2013-2014. We evaluate the contributions of Amazon deforestation and climate change to low precipitation levels using a modelling approach, and address whether similar precipitation anomalies might occur more frequently in a warming world. Precipitation records from INMET show that the dry anomaly extended over a fairly large region to the north of São Paulo. Unique features of this event were anomalous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Barichivich et al [33] found an intensification of Walker's circulation during the late 1990s, associated with strong warming of the tropical Atlantic and cooling of the tropical Pacific. Furthermore, Pattnayak et al [34,35] analyzed the relationship of precipitation in northern and northwestern South America with SST anomalies in the Atlantic after 2000. Therefore, through these interbasin SST gradients, the PDO and AMO SST mean states modulated the CJ and CLLJ variations during the last three decades [30].…”
Section: Of 18mentioning
confidence: 99%
“…Barichivich et al [33] found an intensification of Walker's circulation during the late 1990s, associated with strong warming of the tropical Atlantic and cooling of the tropical Pacific. Furthermore, Pattnayak et al [34,35] analyzed the relationship of precipitation in northern and northwestern South America with SST anomalies in the Atlantic after 2000. Therefore, through these interbasin SST gradients, the PDO and AMO SST mean states modulated the CJ and CLLJ variations during the last three decades [30].…”
Section: Of 18mentioning
confidence: 99%
“…The concentrations of greenhouse gases (GHGs) must fall before 2060 to accomplish the 1.5°C warming objective, whereas to achieve the 2°C warming target, GHGs must fall before 2085 (Sanderson et al., 2016). Due to the change in the concentration of GHGs, the ocean warming pattern changes and hence show different climate response in term of precipitation in the atmosphere (Chadwick et al., 2013; Long et al., 2014; Pattnayak et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…hence show different climate response in term of precipitation in the atmosphere (Chadwick et al, 2013;Long et al, 2014;Pattnayak et al, 2018).…”
mentioning
confidence: 99%
“…Drought events in southeastern Brazil are widely publicized by the national and international news. For example, beginning from austral summer 2013/2014 to 2014/2015, southeastern Brazil suffered a 16-month drought, and by January 2015, the Cantareira reservoir, the main water storage for the metropolitan area of São Paulo, was down to 5% of capacity (Nobre et al 2016;Pattnayak et al 2018). Debate continues over whether anthropogenic effects influenced this event and the past rainfall variability.…”
Section: Introductionmentioning
confidence: 99%